Eco-friendly seeded Fe3O4-Ag nanocrystals: a new type of highly efficient and low cost catalyst for methylene blue reduction. Issue 4 (9th January 2018) - Liu, Y.; Zhang, Y. Y.; Kou, Q. W.; Chen, Y.; Han, D. L.; Wang, D. D.; Lu, Z. Y.; Chen, L.; Yang, J. H.; Xing, S.
Abstract : Hybrid Fe3 O4 -Ag nanocrystals, a new type of highly efficient and reusable catalyst for methylene blue (MB) reduction, are fabricated by a novel seed deposition process. Abstract : Hybrid Fe3 O4 -Ag nanocrystals, a new type of highly efficient and reusable catalyst for methylene blue (MB) reduction, are fabricated by a novel seed deposition process. X-ray diffraction and Mössbauer spectroscopy results show that the developed iron oxides are in a pure magnetite Fe3 O4 phase. Upon manipulating the amount of Ag seeds capsuled on the modified surfaces of Fe3 O4 nanocrystals, the catalytic capacities on the reduction of MB can be precisely adjusted with a tunable fabrication cost control. The linear correlation of the reduced MB concentration versus reaction time catalyzed by our developed hybrid Fe3 O4 -Ag nanocrystals is coherent with pseudo first order kinetics. Importantly, with remarkable recyclability features, the hybrid Fe3 O4 -Ag nanocrystals can be easily separated by applying an external magnetic field. The tailored catalytic performances of the hybrid Fe3 O4 -Ag nanocrystals during MB reduction are attributed to the optimized dynamic electron transfer process, which dominates the electrochemical mechanism wherein the nucleophilic BH4 − ions donate electrons to electrophilic organic MB through Ag seeds in a regulated amount. Such developed hybrid Fe3 O4 -Ag nanocrystals pave the way towards the mass production of highly efficient and low cost catalysts for methylene blue reduction.